2013
DOI: 10.1353/hpu.2014.0000
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Vitamin D and Vitamin D levels Status in Puerto Ricans

Abstract: There is growing and compelling evidence demonstrating the extra-skeletal role of vitamin D and the importance of maintaining adequate levels of this nutrient. Currently, there is very limited information available on the vitamin D status in children and adults in underserved groups, including Puerto Ricans. We assessed the vitamin D status of 4,090 Puerto Ricans living in six geographical regions in the island. Only 31.5% of the studied population had sufficient vitamin D levels (>30 ng/ml). The 18–39 year ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…A study with a smaller sample (n=219) found that 60.3% had low vitamin D status (<30 ng/mL) [23], while in another study (n=4,090), 68.5% had low vitamin D [8]. However, individuals from the present study were different from other studies conducted in PR, as they were selected among an endocrinology health clinic attenders and thus were unlikely to be representative of all individuals from such area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study with a smaller sample (n=219) found that 60.3% had low vitamin D status (<30 ng/mL) [23], while in another study (n=4,090), 68.5% had low vitamin D [8]. However, individuals from the present study were different from other studies conducted in PR, as they were selected among an endocrinology health clinic attenders and thus were unlikely to be representative of all individuals from such area.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States (US), 32% of the total population and 43% of the Hispanics had vitamin D levels below 20 ng/mL [7]. Moreover, in a large sample of Puerto Ricans (n=4,090), 65.8% had vitamin D levels below 30 ng/mL and 24.9% had levels below 20 ng/mL [8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that low VD status is highly prevalent worldwide, and the major determinants are sun exposure and vitamin D intake [25,26]. Another study reported that VD deficiency was highly prevalent among studied Saudi women who suffer from obesity, poor sunlight exposure and poor dietary VD supplementation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Puerto Rico is not an exemption; a study using a large sample size (> 4090 of individuals) found vitamin D deficiency in 24.9% and vitamin D insufficiency in 43.6% [10]. Such high prevalence of low vitamin D status is present even though Puerto Rico is situated near the Equator, with sun exposure all year around and minimal seasonal changes.…”
Section: Introductionmentioning
confidence: 99%